Pengaruh Leverage, Profitabilitas, dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan Sektor Properti di BEI (2021–2024) - Febriana Febriana; Marwan Setiawan; Mulia Indah Purwati (ARZUSIN, 2026)
Research on firm value continues to develop in the field of financial management, but discussions that specifically examine the effects of leverage, profitability, and company growth in the property sector on the Indonesia Stock Exchange during the 2021–2024 period still need to be strengthened. This study aims to analyze the effects of leverage, profitability, and company growth on the firm value of property sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This study employed a quantitative approach with a causal-associative design. The research sample consisted of property sector companies selected through the purposive sampling technique based on the criteria of companies consistently listed during the research period, having complete financial reports, and providing data according to the needs of the study. Data were collected through documentation study of company financial reports and were then analyzed using multiple linear regression with the assistance of SPSS. Before regression analysis was conducted, the data were tested through classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The results show that Debt to Equity Ratio (DER) and Return on Assets (ROA) have negative and significant effects on Price to Book Value (PBV), whereas growth has a positive and significant effect on PBV. Simultaneously, DER, ROA, and growth have a significant effect on PBV, with a coefficient of determination (R²) of 75.7%. These findings contribute to the development of capital structure theory and signaling theory in explaining firm value, while also broadening understanding of the factors that influence firm value in the property sector. The conclusion of the study emphasizes the importance of managing capital structure, profitability, and company growth in a balanced manner in efforts to increase firm value. The implications of this study include theoretical contributions to the financial management literature as well as practical implications for company management and investors in decision-making.